Antimalarial and antimicrobial substances isolated from the endophytic actinomycete, Streptomyces aculeolatus MS1-6. (March 2023) - Kuncharoen, Nattakorn; Bunbamrung, Nantiya; Intaraudom, Chakapong; Choowong, Wilunda; Thawai, Chitti; Tanasupawat, Somboon; Pittayakhajonwut, Pattama
Abstract: Seven undescribed compounds, including four naphthoquinone terpenoids (aculeolatins A – D), one rare 2-nitropyrrole terpenoid (nitropyrrolin F), and two hydroxamate siderophores (aculeolamides A and B) and one further undescribed compound (2, 5, 7-trihydroxy-3, 6-dimethylnaphthalene-1, 4-dione), together with eleven known compounds (arromycin, phenaziterpene A, nitropyrrolin A, heronapyrroles A and B, salaceyin A, 5, 7-dihydroxy-2-isopropylchromone, 1-hydroxyphenazine, 1-methoxyphenazine, 1-acetyl-β-carboline, and N-(2-phenylethyl) acetamide), were isolated from the cultures of the endophytic Streptomyces aculeolatus MS1-6. The structures of the isolated compounds were determined using NMR spectroscopy and corroborated using chemical modification. These compounds exhibited a broad spectrum of biological activities, including antimalarial (IC50 6.03–9.84 μg/mL), antitubercular (MIC 3.13–6.25 μg/mL), anti-plant pathogenic fungal (MIC 25.0–50.0 μg/mL), and antibacterial (MIC 3.03–50 μg/mL) activities; however, they displayed unremarkable cytotoxicity against cancerous (MCF-7 and NCI–H187) and non-cancerous (Vero) cell lines. Graphical abstract: Eight undescribed natural compounds along with eleven known compounds were isolated from the endophytic Streptomyces aculeolatus MS1-6. These isolated compounds exhibited antimalarial, antibacterial, and anti-plant pathogenic fungal activities without obvious cytotoxicity against MCF-7, NCI–H187, and Vero cells. Image 1 Highlights: Eight undescribed natural compounds were isolated from Streptomyces aculeolatus MS1-6. Chemical structures were established by NMR spectroscopic data and chemical modification. Absolute configuration of nitropyrrolin derivative was assigned by Mosher's method. The isolated compounds exhibited antimicrobial activity without significant cytotoxicity.